2017
DOI: 10.1088/1674-1056/26/10/100505
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical energy equipartition of the Toda model with additional on-site potentials

Abstract: We study the dynamical energy equipartition properties in the integrable Toda model with additional uniform or disordered on-site energies by extensive numerical simulations. The total energy is initially equidistributed among some of the lowest frequency linear modes. For the Toda model with uniform on-site potentials, the energy spectrum keeps its profile nearly unchanged in a relatively short time scale. On a much longer time scale, the energies of tail modes increase slowly with time. Energy equipartition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Over the past decades, the study of energy relaxation in anharmonic disordered systems has attracted a lot of interest both theoretically [1][2][3][4][5][6][7][8][9][10][11][12] and experimentally. [13][14][15][16][17][18] In a simple case of harmonic disordered systems, this is relevant to the celebrated Anderson localization phenomenon predicted for noninteracting electrons propagating in uncorrelated random landscapes, [19] which has the strongest effect in one dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, the study of energy relaxation in anharmonic disordered systems has attracted a lot of interest both theoretically [1][2][3][4][5][6][7][8][9][10][11][12] and experimentally. [13][14][15][16][17][18] In a simple case of harmonic disordered systems, this is relevant to the celebrated Anderson localization phenomenon predicted for noninteracting electrons propagating in uncorrelated random landscapes, [19] which has the strongest effect in one dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have addressed this question. The pinned Toda system was studied in [28] where it was found that energy transfer to high-frequency modes is slow and energy equipartition is not observed in the studied time scale. Similar features were observed in the trapped hard rod system [29], where it was observed that the system become chaotic after a characteristic time scale but fails to thermalize even at extremely large times.…”
Section: Introductionmentioning
confidence: 99%